Soccer Violence: Factor and Tackling Mechanism: In the Case of Ethiopia Premier League (Epl) - Kiflu (Ph.D), Alemmebrat (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2020)
In Ethiopia, soccer violence was sporadic, however; these days, it is becoming a growing concern and it extended even outside the stadium. Spectators are reserved to go stadiums in afraid of violence related injuries, this violence damaging the sociocultural and economy of the country, and it also affects the image and development of football as a whole. Despite this, studies were scanty and not properly done. Thus, the purpose of this study was to examine the causes and it’s tackling strategies. A cross-sectional descriptive study was conducted among 137 potential respondents since 1st of January2016 to 31 of October, 2017 using snow ball and stratified random sampling for the qualitative and quantitative data respectively. The interview was analyzed qualitatively while IBM SPSS software version 20was applied as a statistical tool for the analysis of quantitative data. The findings revealed that the chief factors of spectator violence were found to be multifactorial, however; the root cause emerged from players; referees; coaches, spectators; clubs fans, football federation; clubs managers; the media bodies and quality of stadiums. As a means of tackling mechanism the best remedies are discussing the problems with the stakeholders; awareness creation and sustainable education of the communities; strict punishment policy followed by execution of the law are the major ones besides to identifying the most active place of violence, traditionally named as “Katanga”. In conclusion, there is a need to take serious and feasible action on how to curb the problem and how to ensure sustainable and peaceful tournaments before it traumatizing the sport families. The federation should improve also to the quality of stadiums using CCTV and good fence and pay attention on proactive strategies like education as a big weapon than focusing on reactive measure